Mapping quantum state dynamics in spontaneous emission - M. Naghiloo (Nature Portfolio, 2016)
The evolution of a quantum state undergoing radiative decay depends on how the emission is detected. Here, the authors demonstrate how continuous field detection, as opposed to the more common detection of energy quanta, allows control of the back-action on the emitter’s state.